Consumer protection of false halal logo and misleading representation under the consumer Protection Act 1999 - N., Nasihah; Abu Bakar, Elistina; Muhammad Arif, Afida Mastura (Malaysian Consumer and Family Economics Association, 2020)
The law is the most effective mechanism in imposing liability against a supplier or manufacturer in the issue of false halal logo and misleading representation. This is because the law puts the responsibility on the supplier or manufacturer to ensure that they supply a product that is halal as stated. However, the question arises as to whether the rights of the consumers regarding false halal logo and misleading representation were fully protected under the Consumer Protection Act 1999. Therefore, this article aims to analyze the liability of the supplier or manufacturer under the Consumer Protection Act 1999, concerning matters regarding consumers protection in the case of the false halal logo and misleading representation. The findings of this article revealed that the Part II, V, and X of the CPA 1999 are not sufficient to address the liabilities of the supplier or manufacturer on the issue of false halal logo and misleading representation. This study implies that the Consumer Protection Act 1999 should be reviewed in order to provide consumers with better protection. An effort needs to be done to improve the consumer protection laws in Malaysia, thus growing in tandem with the halal industry.